ENHANCING CYBERSECURITY WITH AI: A MACHINE LEARNING APPROACH TO THREAT DETECTION. - Rejina P V (ShodhKosh: Journal of Visual and Performing Arts, 2022)
With Dynamic domain cyber threats involved complexity has increased, causing challenges for traditional protection systems. An Overviewing this paper, we proposed an investigation into the impact of AI (especially ML) in bolstering cybersecurity systems with modern threat detection. The research emphasises on the design and implementation of machine learning algorithms that can detect anomalies, predict possible attacks and learn and adapt to new patterns of threat in real time. Then, a comparative analysis of supervised, unsupervised, and reinforcement learning models is provided while their applicability to requests detection is discussed. In this way, they train and evaluate the models on both real-world datasets and simulated environments. As this analysis proves, detection accuracy, response time, and zero-day attacks capability are all considerably improved compared to traditional rule-based systems after running this data on our machine learning algorithm. Future research regarding the effectiveness and implementation of AI in cybersecurity practices may also help to further develop these new frameworks or evolve how current practices are conducted in terms of machine learning, pattern recognition, and more.